Hydrophobic coating for stabilizing zinc anode as well as preparation method and application of hydrophobic coating
By constructing a hydrophobic coating made of alkyl trimethylammonium bromide and carboxylated cellulose composite on the zinc anode surface of the zinc ion battery, problems such as dendrite formation and corrosion in the battery are solved, and the service life and efficiency of the battery are significantly improved.
Patent Information
- Application Number
- CN202510062047.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
During the circulation process, aqueous zinc ion batteries face problems such as dendrites, corrosion and accumulation of insoluble by-products on the surface of zinc anode, resulting in a shortened battery life and reduced efficiency.
A composite of alkyl trimethyl ammonium bromide and carboxylated cellulose is used as the active material. By anchoring the quaternary ammonium salt group with carboxylate on the carboxylated cellulose, a hydrophobic coating is constructed on the surface of the zinc anode to inhibit corrosion and dendrites.
Effectively inhibit the corrosion of zinc anode and dendrites, improve the service life of zinc ion batteries, and enhance the stability and Coulomb efficiency of the battery.
Smart Images

Figure CN119890300A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, and in particular relates to a hydrophobic coating for stabilizing a zinc anode, and a preparation method and application thereof. Background Art
[0002] Due to the global warming caused by the extensive use of fossil energy by humans, the development of new energy has ushered in opportunities. Compared with lithium-ion batteries, aqueous zinc-ion batteries have significant advantages in safety, cost-effectiveness, eco-friendliness and manufacturing feasibility, making them a more promising choice for large-scale energy storage applications. However, the commercial application of aqueous zinc-ion batteries also faces many challenges, including hydrogen evolution reaction, corrosion and dendrite growth on the zinc anode, which seriously restrict the application of aqueous zinc-ion batteries.
[0003] In order to make zinc-ion batteries a competitive energy storage system, several key issues need to be addressed. First, the metal zinc anode faces the problem of dendrite formation during the cycle. During the battery cycle, zinc dendrites may fall off the electrode, resulting in the formation of "dead zinc", which leads to the loss of active materials and low Coulomb efficiency. In the worst case, the continued growth of these dendrites can penetrate the separator and contact the cathode, resulting in a short circuit in the battery. Therefore, in order to extend the life of zinc-ion batteries, it is crucial to achieve zinc dendrite-free deposition. On the other hand, the zinc anode will corrode during the charge and discharge process, forming an insoluble byproduct Zn4(SO4)OH6·nH2O on the electrode surface, which will hinder the transmission of zinc ions and further aggravate the growth of zinc dendrites. One of the main methods for modifying zinc anodes in aqueous zinc-ion batteries is to build a protective layer on the surface of the zinc anode to achieve uniform zinc deposition while preventing corrosion from the electrolyte. Summary of the invention
[0004] The purpose of the present invention is to provide a hydrophobic coating for stabilizing zinc anodes and a preparation method and application thereof. The hydrophobic coating for stabilizing zinc anodes is prepared by using alkyl trimethyl ammonium bromide and carboxylated cellulose as active materials, and the positively charged hydrophilic quaternary ammonium salt group of alkyl trimethyl ammonium bromide is anchored with the carboxyl group on the negatively charged carboxylated cellulose, and the hydrophobic alkyl group of the quaternary ammonium salt group automatically faces outward, so that a hydrophobic interface can be constructed on the surface of the zinc anode to inhibit the occurrence of corrosion. At the same time, the carboxyl group on the carboxylated cellulose can effectively uniform the zinc ion flux as a zinc-philic site, realize uniform zinc deposition, inhibit the growth of dendrites, and greatly improve the service life of aqueous zinc ion batteries.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a hydrophobic coating for stabilizing zinc anode, the components of which include active material, conductive agent and binder;
[0007] The active material is a complex of alkyltrimethylammonium bromide and carboxylated cellulose.
[0008] Preferably, the alkyltrimethylammonium bromide includes dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide or octadecyltrimethylammonium bromide.
[0009] Preferably, in the active material, alkyltrimethylammonium bromide accounts for 5 to 30 wt.%, and carboxylated cellulose accounts for 70 to 95 wt.%.
[0010] Preferably, the preparation step of the active material comprises: dispersing the alkyltrimethylammonium bromide and the carboxylated cellulose in water, filtering and drying to obtain the active material.
[0011] More preferably, the drying further includes a washing step.
[0012] Optionally, the conductive agent is conductive carbon black.
[0013] Optionally, the binder is polyvinylidene fluoride.
[0014] Preferably, in the hydrophobic coating of the stable zinc anode, the active material accounts for 75-90 wt.%, the conductive agent accounts for 1-15 wt.%, and the binder accounts for 5-15 wt.%.
[0015] The second technical solution of the present invention is to provide a method for preparing the hydrophobic coating of the above-mentioned stable zinc anode, comprising the following steps:
[0016] The active material, the conductive agent and the binder are ground together and then prepared into slurry with an organic solvent. The slurry is coated on the surface of the zinc anode and dried to obtain a hydrophobic coating for stabilizing the zinc anode.
[0017] The third technical solution of the present invention is to provide an anode material, which is obtained by coating the surface of zinc metal or galvanized material with the hydrophobic coating of the above-mentioned stable zinc anode.
[0018] The fourth technical solution of the present invention is to provide an application of the hydrophobic coating of the above-mentioned stable zinc anode in the preparation of an aqueous zinc ion battery.
[0019] The fifth technical solution of the present invention is to provide an application of the above-mentioned anode material in the preparation of an aqueous zinc ion battery.
[0020] The beneficial technical effects of the present invention are as follows:
[0021] The hydrophobic coating for stabilizing the zinc anode provided by the present invention uses a composite of alkyl trimethyl ammonium bromide and carboxylated cellulose as an active material, and utilizes the fact that the positively charged hydrophilic quaternary ammonium salt group of the alkyl trimethyl ammonium bromide can be anchored with the carboxyl group on the negatively charged carboxylated cellulose, and the hydrophobic alkyl group of the quaternary ammonium salt group will automatically face outward, so that a hydrophobic interface can be constructed on the surface of the zinc anode to inhibit the occurrence of corrosion. At the same time, the carboxyl group on the carboxylated cellulose can effectively uniformize the zinc ion flux as a zinc-philic site, realize uniform zinc deposition, inhibit the growth of dendrites, and greatly improve the service life of the aqueous zinc ion battery.
[0022] The preparation method provided by the present invention has the advantages of low cost, simple process, high safety, etc., and can prepare an aqueous zinc ion battery coating with excellent performance, which is of great significance for promoting the commercial application of aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a contact angle diagram of the electrode modified with the composite material prepared in Example 1 and 2M zinc sulfate electrolyte.
[0024] Figure 2 Coulombic efficiency diagram of a half-cell assembled with an electrode modified with the composite material prepared in Example 1 and copper foil.
[0025] Figure 3 The electrode modified with the composite material prepared in Example 1 and the unmodified zinc anode of Comparative Example 1 were assembled into symmetrical cells at 1 mA·cm -2 Current density and 1mAh·cm -2 The charge and discharge cycle diagram under the conditions of .
[0026] Figure 4 The rate performance diagram of a symmetrical battery assembled with electrodes modified with the composite material prepared in Example 1.
[0027] Figure 5 This is the BET diagram of the active material used in Example 1.
[0028] Figure 6 The electrode modified with the composite material prepared in Example 1 and the unmodified zinc anode of Comparative Example 1 were assembled into symmetrical cells at 1 mA·cm -2 Current density and 1mAh·cm -2 SEM images after 100 charge and discharge cycles under the same conditions, wherein (a) is the SEM image of the anode of Example 1, and (b) is the SEM image of the anode of Comparative Example 1.
[0029] Figure 7 The electrode modified with the composite material prepared in Example 1 and the unmodified zinc anode of Comparative Example 1 were assembled into symmetrical cells at 1 mA·cm -2 Current density and 1mAh·cm-2 Static cycle diagram under conditions.
[0030] Figure 8 The electrodes modified by the composite material prepared in Example 1 were assembled into a symmetrical battery at 2 mA·cm -2 Cycle diagram at a discharge depth of 60.23% under current density. DETAILED DESCRIPTION
[0031] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0032] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0033] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The active material used in the embodiments of the present invention is prepared by the following steps:
[0036] 0.4 g of carboxylated nanocellulose and 0.04 g of hexadecyltrimethylammonium bromide were added to 10 mL of aqueous solution in sequence, and the mixture was fully stirred for 30 min and filtered. The precipitate was centrifuged alternately with deionized water and anhydrous ethanol three times, and finally dried in an oven at 80 °C for 4 h to obtain the active material (CMC-CTAB).
[0037] Example 1
[0038] The active material, conductive carbon black, and polyvinylidene fluoride were mixed in a mass ratio of 9:1:1, fully ground in an agate mortar, added with N-methylpyrrolidone, and mixed evenly to obtain a slurry. The obtained slurry was then spin-coated on a 1 cm 2 The circular zinc foil surface was dried in vacuum at 60 °C for 6 h to obtain an electrode modified with a composite material.
[0039] The electrode modified by the composite material was used as the anode of the battery, the glass fiber membrane was used as the separator, 2M zinc sulfate was used as the electrolyte, and CR 2032 stainless steel was used as the battery shell to assemble a button-type zinc ion battery. The assembled symmetrical battery was -2 Current density and 1mAh·cm -2 Under the condition of stable cycle for more than 1200h.
[0040] Example 2
[0041] The active material, conductive carbon black, and polyvinylidene fluoride were mixed in a mass ratio of 18:1:2, fully ground in an agate mortar, added with N-methylpyrrolidone, and mixed evenly to obtain a slurry. The obtained slurry was then spin-coated on a 1 cm 2 The circular zinc foil surface was dried in vacuum at 60 °C for 6 h to obtain an electrode modified with a composite material.
[0042] The electrode modified by the composite material was used as the anode of the battery, the glass fiber membrane was used as the separator, 2M zinc sulfate was used as the electrolyte, and CR 2032 stainless steel was used as the battery shell to assemble a button-type zinc ion battery. The assembled symmetrical battery was -2 Current density and 1mAh·cm -2 Under the condition of stable cycle for more than 800h.
[0043] Comparative Example 1
[0044] 1cm 2 The circular zinc foil is used as electrode.
[0045] The above electrode was used as the anode of the battery, the glass fiber membrane was used as the separator, 2M zinc sulfate was used as the electrolyte, and CR 2032 stainless steel was used as the battery shell to assemble a button-type zinc ion battery. The assembled symmetrical battery was -2 Current density and 1mAh·cm -2 Under the condition of stable circulation, it can last for more than 200h.
[0046] Comparative Example 2
[0047] Carboxylated cellulose, conductive carbon black, and polyvinylidene fluoride were mixed in a mass ratio of 9:1:1, fully ground in an agate mortar, added with N-methylpyrrolidone, and mixed evenly to obtain a slurry. The obtained slurry was then spin-coated on a 1 cm 2 The circular zinc foil surface was dried in vacuum at 60 °C for 6 h to obtain an electrode modified with a composite material.
[0048] The electrode modified by the composite material was used as the anode of the battery, the glass fiber membrane was used as the separator, 2M zinc sulfate was used as the electrolyte, and CR 2032 stainless steel was used as the battery shell to assemble a button-type zinc ion battery. The assembled symmetrical battery was subjected to a load of 5 mA·cm-2 Current density and 1mAh·cm -2 Under the condition of stable cycle for more than 700h.
[0049] Figure 1 This is a contact angle diagram of the electrode modified with the composite material prepared in Example 1 and 2M zinc sulfate electrolyte.
[0050] Depend on Figure 1 It can be seen that the interface of zinc anode modified by CMC-CTAB is in a hydrophobic state, indicating that the coating has a certain corrosion resistance.
[0051] Figure 2 The coulomb efficiency diagram of a half-cell (the separator is a glass fiber membrane and the electrolyte is 2M zinc sulfate) assembled with an electrode modified with the composite material prepared in Example 1 and copper foil.
[0052] Depend on Figure 2 It can be seen that the half-cell assembled with CMC-CTAB modified zinc anode and copper foil can be stably cycled for more than 1200 cycles.
[0053] Figure 3 The electrode modified with the composite material prepared in Example 1 and the unmodified zinc anode of Comparative Example 1 were assembled into symmetrical cells at 1 mA·cm -2 Current density and 1mAh·cm -2 The charge and discharge cycle diagram under the conditions of .
[0054] Depend on Figure 3 It can be seen that the symmetric battery composed of CMC-CTAB modified zinc anode can be stably cycled for more than 2500 h, while the unmodified zinc foil can only be cycled for 207 h.
[0055] Figure 4 The rate performance diagram of a symmetrical battery assembled with electrodes modified with the composite material prepared in Example 1.
[0056] Depend on Figure 4 It can be seen that the symmetric battery assembled with CMC-CTAB modified zinc anode can achieve stable cycling at different current densities.
[0057] Figure 5 This is the BET diagram of the active material used in Example 1.
[0058] Depend on Figure 5 It can be seen that CMC-CTAB material has a mesoporous structure.
[0059] Figure 6 The electrode modified with the composite material prepared in Example 1 and the unmodified zinc anode of Comparative Example 1 were assembled into symmetrical cells at 1 mA·cm -2 Current density and 1mAh·cm-2 SEM images after 100 charge and discharge cycles under the same conditions, wherein (a) is the SEM image of the anode of Example 1, and (b) is the SEM image of the anode of Comparative Example 1.
[0060] Depend on Figure 6 It can be seen that after the same number of cycles at the same current density, dendrites are distributed all over the unmodified zinc foil, while no dendrites are produced on the CMC-CTAB modified zinc foil.
[0061] Figure 7 The electrode modified with the composite material prepared in Example 1 and the unmodified zinc anode of Comparative Example 1 were assembled into symmetrical cells at 1 mA·cm -2 Current density and 1mAh·cm -2 Static cycle diagram under conditions.
[0062] Depend on Figure 7 It can be seen that under the harsh conditions of static cycling, the symmetrical battery composed of CMC-CTAB modified zinc anode can still cycle for more than 700 hours.
[0063] Figure 8 The electrodes modified by the composite material prepared in Example 1 were assembled into a symmetrical battery at 2 mA·cm -2 Cycle diagram at a discharge depth of 60.23% under current density.
[0064] Depend on Figure 8 It can be seen that the zinc foil modified with CMC-CTAB can be stably cycled for more than 150 h at a discharge depth of 60.23%.
[0065] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A hydrophobic coating for stabilizing zinc anodes, characterized in that: The components include active materials, conductive agents and binders; The active material is a complex of alkyltrimethylammonium bromide and carboxylated cellulose.
2. The hydrophobic coating for stabilizing zinc anode according to claim 1, characterized in that: The alkyl trimethyl ammonium bromide includes dodecyl trimethyl ammonium bromide, tetradecyl trimethyl ammonium bromide, hexadecyl trimethyl ammonium bromide or octadecyl trimethyl ammonium bromide.
3. The hydrophobic coating for stabilizing zinc anode according to claim 1, characterized in that: In the active material, alkyl trimethyl ammonium bromide accounts for 5-30 wt.%, and carboxylated cellulose accounts for 70-95 wt.%.
4. The hydrophobic coating for stabilizing zinc anode according to claim 1, characterized in that: The preparation step of the active material comprises: dispersing the alkyl trimethyl ammonium bromide and the carboxylated cellulose in water, filtering and drying to obtain the active material.
5. The hydrophobic coating for stabilizing zinc anode according to claim 4, characterized in that: The method further comprises a washing step before the drying.
6. The hydrophobic coating for stabilizing zinc anode according to claim 1, characterized in that: In the hydrophobic coating of the stable zinc anode, the active material accounts for 75-90 wt.%, the conductive agent accounts for 1-15 wt.%, and the binder accounts for 5-15 wt.%.
7. A method for preparing a hydrophobic coating for stabilizing a zinc anode according to any one of claims 1 to 6, characterized in that: The following steps are involved: The active material, the conductive agent and the binder are ground together and then prepared into slurry with an organic solvent. The slurry is coated on the surface of the zinc anode and dried to obtain a hydrophobic coating for stabilizing the zinc anode.
8. An anode material, characterized in that: The hydrophobic coating of the stable zinc anode according to any one of claims 1 to 6 is applied on the surface of zinc metal or galvanized material to obtain the stable zinc anode.
9. Use of the hydrophobic coating for stabilizing zinc anodes according to any one of claims 1 to 6 in the preparation of aqueous zinc ion batteries.
10. Use of the anode material according to claim 8 in preparing an aqueous zinc ion battery.